Concrete incorporated with optimum percentages of recycled Polyethylene Terephthalate (PET) bottle fiber - Shahidan, S.; Ranle, N. A.; Mohd Zuki, S. S.; Khalid, F. Sheikh; Ridzuan, A. R. M.; Nazri, F. M. (Penerbit UTHM, 2018)
Plastic solid waste generation increases every year with the current consumption habit prevalent in the society nowadays. The improper disposal of plastic has been a major concern to the environment as it is not easily degradable. The issue of environmental pollution caused by Polyethylene Terephthalates (PET) has been extensively discussed and the best solution proposed is recycling. Therefore, one of the potential means to the problem is to recycle polyethylene terephthalate (PET) in the construction industry as fiber concrete (FC). FC is a composite material resulting from the addition of fibers to ordinary concrete. The objective of this research is to determine the mechanical properties and the optimum percentages of recycled polyethylene terephthalate (PET) fibers in ordinary concrete. In this study, straight and irregular recycled polyethylene terephthalate (PET) fibers were used. The fibers were simply cut from polyethylene terephthalate (PET) plastic bottles. The length and width of recycled polyethylene terephthalate (PET) fiber were fixed at 50 mm and 5 mm respectively. The percentages of recycled PET fibers added in the concrete mix were 0.5%, 1%, 1.5% and 2.0% respectively according to the volume of concrete to continue research of Ochi et al. (2007). A water-cement ratio of 0.45 was accepted for all ranges. The tests that were conducted included the slump test, compressive strength test and splitting tensile strength test. The specimens were tested on day 7 and day 28 after the concrete was mixed. The results obtained from each test indicated that when the percentage of recycled polyethylene terephthalate (PET) fiber used increases, the values obtained from the slump test and compressive strength test decreases while the value obtained from the splitting tensile test increases.